Factors influencing surgical treatment decisions for breast cancer: a qualitative exploration of surgeon and patient perspectives - Dicks, E. (Curr Oncol, 2019)
BACKGROUND: The rate of mastectomy is much higher in Newfoundland and Labrador than in any other province in Canada, even for women diagnosed at an early stage. In this paper, we present qualitative data from women who have made a decision for surgical treatment and from breast surgeons in an effort to better explicate factors influencing breast cancer (bca) surgical decision-making. METHODS: The study’s descriptive, qualitative design involved holding interviews with breast surgeons and holding focus groups and interviews with women who were offered the choice of breast-conserving surgery (bcs) or mastectomy (mt). RESULTS: Participants included 35 women and 13 surgeons. High interest in mt and increasing requests for prophylactic contralateral mt were evident. A host of factors—clinical, demographic, psychosocial, education-related, and cultural—influenced the decisions. A key factor for women was fear of recurrence and a need to “just get rid of it,” but the experiences of others also influenced the decisions. Life stage and family considerations also factored prominently into women’s decisions. CONCLUSIONS: Women with early-stage bca more often chose mt and often demanded prophylactic removal of the healthy breast. Findings highlight the importance of ensuring that women at average risk are appropriately counselled about the low likelihood of a subsequent contralateral bca and the lack of survival benefit associated with prophylactic contralateral mt. Findings also revealed other areas of presurgical discussion that might help women think through their personal circumstances and values so as to encourage informed surgical decisions.